Local piezoelectric response of single poly(vinylidene fluoride) electrospun fibers - Sencadas, Vitor (2013)
It is shown that electrospun poly(vynilidene ﬂuoride) nanoﬁbers are fully poled right after preparation and show b-phase contents of 70%, therefore being able to be implemented into electroactive devices without further processing steps. Further,the local piezoelectric properties of individual electrospun ﬁbers have been studied by piezoresponse force microscopy. Piezoelectric response, polarization switching, and nanoscale patterning of the ﬁbers have been demonstrated.